Time and History in Theological Ethics: The Work of James Gustafson - Hauerwas, Stanley (Journal of religious ethics, 1985)
This essay traces Gustafson's understanding of the methodological significance of history and time for theological ethics. I argue that Gustafson qualifies his original thoroughgoing historicist perspective in the interest of developing a natural theology and ethics. His continuing emphasis on a historical perspective, I suggest, is best understood by attending to his recommendation that the theologian's task is best captured by the image of the "participant."